Neurologic dengue manifestations associated with intrathecal specific immune response - Puccioni-Sohler, M; Soares, C N; Papaiz-Alvarenga, R; Castro, M J C; Faria, L C; Peralta, J M (Neurology, 2009)
Dengue infection is caused by a flavivirus, with 4 virus serotypes (types 1 to 4). The serotypes 2 and 3 represent the principal agents related to nervous system involvement. Neurologic involvement occurs in 4%-5% of dengue infection cases. The major mechanisms of the disease may be related to direct viral infection or postinfectious autoimmune process. The detection of intrathecal synthesis of specific antibodies has been used to support neurologic diagnosis as a proof of local reaction. It may be quantitatively calculated by the specific antibody index. To determine if patients with neurologic manifestations associated with dengue produce specific antibodies in the CNS and to determine the antibodies' clinical and pathophysiologic relevance. CSF and serum were evaluated for dengue immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies by ELISA and for intrathecal synthesis of IgG antibodies to the dengue virus. Subjects included 10 patients IgM seropositive for dengue virus diagnosed with myelitis, encephalitis, optic neuromyelitis, or Guillain-Barré syndrome. All patients had IgG and IgM antibodies to dengue virus in their sera; 7 were IgM positive and 9 were IgG positive for dengue virus in CSF. Only the 3 patients with myelitis had intrathecal synthesis of specific IgG antibodies. Intrathecal synthesis of antibodies to dengue virus occurs in the CNS. It may be used as a marker of myelitis associated with dengue, and it seems to be related to the pathogenesis of spinal cord disease due to direct viral invasion.